SAFER AND FURTHER REPRODUCIBLE INDUCTION METHOD OF ANTI-OBESITY ACTIVITY USING GlcN - AOKI HIDENORI (2017)
PROBLEM TO BE SOLVED: To provide anti-obesity activity-inducing methods with further excellent reproducibility and safety using GlcN, the methods revealing the relation of the amount of carbohydrate intake, body weight variation, side effect incidence rate, and the like to GlcN dose, causing body weight loss in a very short period of time repeatedly, and also improving the side effects of digestive systems, such as diarrhea and abdominal bloating.SOLUTION: The subject is solved by that each value of the carbohydrate intake amount which is acceptable at present (Iog/weight g), the coefficient of effective limit (Emax/10±100), the GlcN oral dose which is acceptable at present (Dpo/weight g), the body weight of a user at present (X/weight kg), the constant of dose limit (0.3), and the cumulative dose of GlcN from the last defecation time to the current time (Et/weight g) has the relation with the following formula.SELECTED DRAWING: Figure 1 【課題】ＧｌｃＮの投与量に対する、糖質摂取量・体重変化量・副作用の発症率等の関係を明らかにし、ごく短期間で体重の減少を繰り返しもたらすと共に、下痢や腹部膨満感などの消化器系の副作用をも改善させる、ＧｌｃＮを用いたより再現性・安全性に優れた抗肥満活性の誘導方法を提供する。【解決手段】現時点で許容し得る糖質摂取量（Ｉｏｇ／重量ｇ）、作用限界係数（Ｅｍａｘ／１０3±１００）、現時点で許容し得るＧｌｃＮの経口投与量（Ｄｐｏ／重量ｇ）、現時点での使用者の体重（Ｘ／重量ｋｇ）、投与限界定数（０．３）、最後の排便時間から現在時間までのＧｌｃＮの累計投与量（Ｅｔ／重量ｇ）、の各値が下記の数式の関係にある事により、前記課題を解決させる事を特徴とする。【選択図】図１